Predictors of Remission of Acromegaly following Surgical Treatment in Growth Hormone-Secreting Pituitary Adenoma - Konar, Subhas; Yeole, Ujwal; Shukla, Dhaval; Bhat, Dhananjaya I.; Sadashiva, Nishanth; Devi, Bhagavatula Indira (Journal of Neurological Surgery Part B: Skull Base, 2023)
Background and Objective Surgery is the treatment of choice for growth hormone (GH)-secreting pituitary adenoma. The remission of random GH depends on various factors. We aimed to evaluate the predictors related to remission of random GH following surgical treatment.Methods We collected the data retrospectively from the chart review from a single unit of neurosurgery. The diagnostic criteria for remission were a random GH < 1 ng/mL or nadir GH < 0.4 ng/mL after an oral glucose tolerance test.Results Data from a total of 110 (females 62 [56.4%]) patients were available for follow-up and were analyzed. The mean age was 36.5 years (14–69 years). Vision impairments were seen in 39 (35.5%) patients. The mean duration of symptoms before surgery was 34 months. The mean volume of the tumor was 7.2 mL (0.44–109.8 mL). Knosp grade 3 and 4 tumors were seen in 41.5% of cases. The mean preoperative random GH level was 68.9 ng/mL. Transsphenoidal surgery was done in 107 (97.3%) cases. The gross total resection could be done in 36 (32.7%) cases. At 3 months, 25 (26%) patients had a biochemical remission. In univariable analysis, lower Knosp grade, preoperative GH level < 40 ng/mL, gross total resection, and male gender were associated with remission at 3 months. In regression analysis, preoperative GH and male gender were related to remission at 3 months.Conclusion The preoperative GH level < 40 ng/mL is associated with higher chances of remission after surgery for GH-secreting pituitary adenoma.
Keywords: pituitary adenoma; giant pituitary adenoma; invasive pituitary adenoma; transsphenoidal surgery